2014
DOI: 10.3892/or.2014.3331
|View full text |Cite
|
Sign up to set email alerts
|

Induced IGF-1R activation contributes to gefitinib resistance following combined treatment with paclitaxel, cisplatin and gefitinib in A549 lung cancer cells

Abstract: Abstract. Gefitinib demonstrates excellent performance in the treatment of lung adenocarcinoma patients; yet, there was no added benefit in combination with chemotherapy as reported in a phase III clinical trial. For exploring the mechanism of the failed combination therapy in lung cancer, in the present study, four therapy assessment groups, including a control group, a chemotherapy group [paclitaxel + cisplatin (TP)], a gefitinib monotherapy group (G) and a combination group [paclitaxel + cisplatin + gefitin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…A large body of evidence has indicated that IGFIR plays important roles in regulating tumor resistance to cisplatin. 30,31 Interestingly, we also found that forced overexpression of miR-100 promoted the effects of cisplatin in osteosarcoma cells, promoted apoptosis, and increased the activity of caspase-3. Thus, it is important that an miR-100 restoration approach may offer a new modulation strategy to overcome chemoresistance to cisplatin treatment in osteosarcoma.…”
Section: Discussionmentioning
confidence: 75%
“…A large body of evidence has indicated that IGFIR plays important roles in regulating tumor resistance to cisplatin. 30,31 Interestingly, we also found that forced overexpression of miR-100 promoted the effects of cisplatin in osteosarcoma cells, promoted apoptosis, and increased the activity of caspase-3. Thus, it is important that an miR-100 restoration approach may offer a new modulation strategy to overcome chemoresistance to cisplatin treatment in osteosarcoma.…”
Section: Discussionmentioning
confidence: 75%
“…A549 cells are human adenocarcinomic alveolar basal epithelial cells that were developed by culturing explanted lung cancer tissue of a male patient [ 15 ]. These cells are widely used as a preclinical research model to develop new treatments for lung cancer [ 16 ] and are known to express high levels of ADLH [ 17 ], making them an appropriate cell model for our study purpose.…”
Section: Introductionmentioning
confidence: 99%
“…There are contradictory reports on the relationship of IGF1R and acquired resistance in many human cancers. In NSCLC (Non-Small Cell Lung Cancer) cell lines, IGF1R activation could contribute to gefitinib resistance and give rise to the failure of the combination therapy [ 24 , 25 ]. HCC (Hepatocellular Carcinoma) cells exhibited strong gefitinib resistance and the levels of phosphorylation in IGF1R and AKT were dramatically increased after drug treatment [ 26 ].…”
Section: Discussionmentioning
confidence: 99%